2022
DOI: 10.1111/jfpp.16952
|View full text |Cite
|
Sign up to set email alerts
|

Application of ultrasound to the organic cornelian cherry (Cornus masL.) vinegar: Changes in antibacterial, antidiabetic, antihypertensive, and anticancer activities

Abstract: In this study, to determine their alternative/complementary properties, organic cornelian cherry vinegar samples prepared by traditional (CCV), thermal pasteurization (P‐CCV), and ultrasound (UT‐CCV) methods were tested for antibacterial, antidiabetic, antihypertensive, and anticancer activities. As a result of response surface methodology optimization, the bioactive compounds were increased. With ultrasound treatment, the total phenolic content increased by 4.6%. The antibacterial activity was detected in all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
3
6
0
Order By: Relevance
“…As a result, it was determined that ultrasound treatment increased the bioactive components of hawthorn vinegar. This result shows similarities with the literature, as many studies have shown that ultrasound treatments have similar advantages over thermal pasteurization [ 24 , 29 , 31 ]. However, the antioxidant contexts derived from using the thermal pasteurization processing method (DPHH: 54.86%; CUPRAC: 60.22%; Flavonoid: 13.18 mgCE/100 mL; Total Phenolic: 104.22 mgGAE/100 mL) were lower than those derived from using normal vinegar processing (DPHH: 57.39%; CUPRAC: 63.55%; Flavonoid: 14.22 mgCE/100 mL; Total Phenolic: 110.58 mgGAE/100 mL).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…As a result, it was determined that ultrasound treatment increased the bioactive components of hawthorn vinegar. This result shows similarities with the literature, as many studies have shown that ultrasound treatments have similar advantages over thermal pasteurization [ 24 , 29 , 31 ]. However, the antioxidant contexts derived from using the thermal pasteurization processing method (DPHH: 54.86%; CUPRAC: 60.22%; Flavonoid: 13.18 mgCE/100 mL; Total Phenolic: 104.22 mgGAE/100 mL) were lower than those derived from using normal vinegar processing (DPHH: 57.39%; CUPRAC: 63.55%; Flavonoid: 14.22 mgCE/100 mL; Total Phenolic: 110.58 mgGAE/100 mL).…”
Section: Resultssupporting
confidence: 86%
“…In contrast, the product’s nutritional value is enhanced [ 23 , 24 , 25 , 26 , 27 ]. Ultrasound treatment and thermal pasteurization positively affect the antioxidant and phenolic content of fruit, fruit juices, and vinegar [ 28 , 29 , 30 , 31 ]. The main components and bioactive compounds of hawthorn vinegar have been revealed in many studies.…”
Section: Introductionmentioning
confidence: 99%
“…These methods cannot effectively remove pesticides and other toxic compounds and produce toxic by-products and secondary pollution in foodstuffs [3] , [11] , [12] , [13] . Some intense processing conditions of conventional processing may influence food's nutritional components and sensory quality [14] , [15] , [16] , [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Fruit vinegars (FVs) are submerge‐fermented liquids and have been consumed as preservatives, condiments, and beverages, involved in many people's daily diet (Ousaaid et al., 2022). Many studies have proved that FVs possessed a wide spectrum of physiological functions, including antihypertensive effects (Lee et al., 2017), bacteriostatic actions (Hammouda et al., 2021), and antidiabetic activities (Erdal et al., 2022). Thus, FVs are candidates for dietary supplements with several potential preventive effects on human disorders.…”
Section: Introductionmentioning
confidence: 99%